The effectiveness of training based on Bandura's self-efficacy theory on hemodialysis patients' resilience during the COVID-19 outbreak: A quasi-experimental study - Atena Ghorbani Hanouj; Maryam Khandan; Yunes Jahani (Shahrekord University of Medical Sciences, 2023)
Background and aims: The COVID-19 outbreak has caused many psychological problems among different groups of society, particularly hemodialysis patients. There is little data on the benefits of resilience as a protective factor for adaptation to specific and threatening situations in such patients. Hence, this study aimed to examine the effects of training based on Bandura's self-efficacy theory on the resilience of hemodialysis patients in the southeast of Iran in 2020 during the COVID-19 outbreak. Methods: This quasi-experimental study was conducted on 140 hemodialysis patients in southeast Iran. The participants were selected by convenient sampling and randomly assigned to control (n=70) and experimental (n=70) groups. Educational content was provided over ten sessions of face-to-face 20-30 minutes to the experimental group, and the control group received routine training. Data were collected via the Connor-Davidson Resilience Scale and analyzed by SPSS version 16 using descriptive and inferential statistics. Results: The mean resilience scores in the experimental and control groups before the intervention were 51.94±11.11 and 53.79±16.04, and after the intervention, 53.27±10.39 and 73.86±13.16, respectively. There was a significant difference between the two groups after the intervention (P<0.05). Conclusion: The findings denote the self-efficacy training program based on Bandura's theory improved resilience in the patients undergoing hemodialysis during the COVID-19 outbreak. Hence, nursing planners and policymakers are recommended to develop some measures for facilitating self-efficacy training programs for hemodialysis patients.